On generalizations of the Jacobsthal sequence - Aydin, Fugen Torunbalci (BULGARIAN ACAD SCIENCE, 2018)
In this paper, the generalized Jacobsthal and generalized complex Jacobsthal and generalized dual Jacobsthal sequences using the Jacobsthal numbers are investigated. Also, special cases of these sequences are investigated. Furthermore, recurrence relations, vectors, the golden ratio and Binet's formula for the generalized Jacobsthal sequences and generalized dual Jacobsthal sequences are given.
Keywords: Jacobsthal number; Jacobsthal-Lucas number; Jacobsthal sequence; Generalized Jacobsthal sequence; Generalized complex Jacobsthal sequence; Generalized dual Jacobsthal sequence; QUATERNIONS; POLYNOMIALS; NUMBERS; Mathematics